Associations of Autistic Traits and Autism with Incontinence and Constipation in a UK Birth Cohort. - Gyamenah, Prince; Burrows, Kimberley; Rai, Dheeraj; Joinson, Carol (Journal of Autism & Developmental Disorders, 2026)
There is evidence that children with autism/autistic traits have higher risks of incontinence and constipation, but no studies have examined this in a large community-based cohort. Aim/Research question: are autistic traits and diagnosed autism prospectively associated with increased odds of incontinence and constipation in children and adolescents? This was a population-based cohort study based on data from the Avon Longitudinal Study of Parents and Children (n = 4233–4490 at age 9 years; n = 3403–3697 at age 14). We used multivariable logistic regression to examine associations of parent-reported autistic traits (sociability, repetitive behaviours, social-communication, coherence) (at ages 3–9 years) and autism with incontinence (bedwetting, daytime-wetting, soiling) and constipation (parent-reported at age 9, self-reported at age 14). We adjusted for parity, maternal age at delivery, child's sex and developmental level, maternal depression, and anxiety (antenatal and postnatal), and indicators of family socioeconomic status. Social-communication and speech coherence difficulties showed the strongest associations with incontinence, e.g., adjusted odds ratio (OR) and 95% confidence interval (CI) for the association between social-communication difficulties and daytime-wetting was 2.21 (1.47–3.32) and for coherence was 2.34 (1.60–3.43). The odds of soiling were also higher in children with social-communication (OR: 1.88, 95% CI 1.28–2.75) and coherence difficulties (OR: 2.04, 95% CI 1.43–2.93). Diagnosed autism was only associated with an increase in the odds of daytime-wetting (OR: 3.18, 95% CI 1.44–7.02). At 14 years, there was less evidence of associations between autistic traits and incontinence but there was evidence of associations between autistic traits and constipation: social-communication (OR: 1.68, 95% CI 1.13–2.49), coherence difficulties (OR: 1.64, 95% CI 1.11–2.41). Early assessment and treatment of incontinence/constipation should be considered for children with autistic traits.